Application of Learning Model Student Teams Achievement Division (STAD) to Improve Student Achievement of Class X TPTU 2 SMKN 2 Metro - Ato (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study aims to determine the effectiveness of the use of the Student Teams Achievement Division (STAD) learning model in Basic Electricity and Electronics (DLE) subjects in class X Air Conditioning and Air Conditioning Engineering 2 Academic Year 2019/2020 Semester 2 at SMKN 2 Metro. This study uses Classroom action research with two research cycles. The study population was all class X students of the Pendinghin and Air Conditioning Engineering expertise program, while the research sample was taken from one class, namely class X TPTU 1. The results of this classroom action research indicated that the application of the Student Teams Achievement Division (STAD) learning model in learning activities was good. in the classroom and the workshop can overcome obstacles that arise during the implementation of learning. Indicators of the success of using this method are based on observations, namely the decreased level of student passivity in participating in learning which includes: student inactivity in responding to the perceptions given by the teacher when giving material decreased from 11 students to 5 students, students who were not active in group learning activities decreased from 10 students become 4 students by reducing the number of study group members and students who have not done group assignments correctly and thoroughly decreasing from 11 students to 6 students, and students whose learning outcomes have not been completed decreases from 12 students to 2 students.